2003
DOI: 10.1128/iai.71.4.1650-1655.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity of Antibodies against PorA after Vaccination with a Meningococcal B Outer Membrane Vesicle Vaccine

Abstract: The cross-reactivity of PorA-specific antibodies induced by a monovalent P1.7-2,4 (MonoMen) and/or a hexavalent (HexaMen) meningococcal B outer membrane vesicle vaccine (OMV) in toddlers and school children was studied by serum bactericidal assays (SBA). First, isogenic vaccine strains and PorA-identical patient isolates were compared as a target in SBA, to ensure that the vaccine strains are representative for patient isolates. Geometric mean titers (GMTs) in SBA against patient isolates with subtypes P1.5-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 15 publications
4
22
0
Order By: Relevance
“…Interestingly, in the SBA assay, the phenotypically identical strain M01 240149 only had half the number of subjects attaining Ն4-fold increases, although the percentage of subjects with an SBA titer of Ն4 was similar. These findings are similar to previous reports wherein different P1.7-2,4 wild-type isolates have demonstrated significantly different SBA activity (13,44), suggesting that the standardization of strains between laboratories is crucial for the compatibility of the data. For the United Kingdom representative isolates, the SBA responses were generally poor, with low percentages of subjects achieving Ն4-fold increases.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, in the SBA assay, the phenotypically identical strain M01 240149 only had half the number of subjects attaining Ն4-fold increases, although the percentage of subjects with an SBA titer of Ն4 was similar. These findings are similar to previous reports wherein different P1.7-2,4 wild-type isolates have demonstrated significantly different SBA activity (13,44), suggesting that the standardization of strains between laboratories is crucial for the compatibility of the data. For the United Kingdom representative isolates, the SBA responses were generally poor, with low percentages of subjects achieving Ն4-fold increases.…”
Section: Discussionsupporting
confidence: 82%
“…The variable regions 1 (VR1's) of the two PorA antigens (the P1.7-2 and P1.7 epitopes) are the same except for a deletion of three amino acids in P1.7-2, masking this epitope from interacting with a P1.7-specific monoclonal antibody (35,60), whereas the two VR2's (the P1.4 and P1.16 epitopes) are very different (35). Studies performed by the use of various antibody assays, including immunoblotting, have demonstrated that PorA antibodies induced by MenBvac, MeNZB, or the corresponding PorA components in the Dutch PorA OMV vaccines are mainly directed against VR2 in P1.7,16 and P1.7-2,4 PorA (26,34,42,55,62,63). The VR1 epitopes seem to be less immunogenic than VR2.…”
Section: Discussionmentioning
confidence: 99%
“…However, these researchers showed that there was no association between a low level of PorA expression and vaccination status, as there were equal numbers of meningococci expressing low levels of PorA in immunized and nonimmunized children. Vermont and colleagues (33) showed that immune responses directed against meningococci with significantly different porA VR2 sequences were reduced, whereas responses against isolates with porA variants that had most of the VR2-4 sequence conserved were less affected. Whether people challenged with meningococci demonstrating the P1.7-2,4 deletions or the transcriptional variations detected in this study would be protected by anti-P1.7-2,4 antibodies induced by a strain-specific vaccine cannot be determined from this study but is currently being investigated.…”
Section: Discussionmentioning
confidence: 99%